Peyzaj mimarlığı eğitiminin ekolojik boyutunun farklı fakülteler çerçevesinde değerlendirilmesi - Güzel, Zehra Tuğba (Fen Bilimleri Enstitü, 2020)
Dünya'da ilk kez Harvard Üniversitesinde 1900'lü yıllarda başlayan peyzaj mimarlığı eğitimi günümüze kadar yerel ve ulusal birçok üniversitenin eğitim programında yer almaktadır. Peyzaj mimarlığı eğitimi ülkelere, çalışılan konulara, üniversitelere ve fakültelere bağlı olarak çeşitlilik göstermektedir. Fakültelere göre programların müfredat, vizyon, misyon ve ders işleyiş şekillerinin farklılıklar göstermesi, peyzaj mimarlığı eğitiminde üniversitelerin güncel çevresel sorunlara farklı yaklaşımlar, bakış açıları geliştirmesine sebep olmaktadır. Bazı fakülteler bitkisel materyallerin korunması ve planlanmasına odaklanırken bazıları peyzaj tasarımına, bazıları peyzaj projelerinin uygulanması yönüne odaklanmaktadır. Fakat unutulmaması gerekir ki bir peyzaj mimarı yukarıda bahsedilen tüm alanlarda uzman kabul edilerek mezun olmaktadır ve her şartta, her çevresel koşulda mesleğini icra edebilmelidir. Peyzaj mimarları insanların doğaya olan ihtiyacını doğal dengeyle birlikte düşünmektedir. Konuyla ilgili olarak geliştirilen ekolojik tabanlı sürdürülebilir yaklaşımlar peyzaj mimarlığı disiplininin en önemli konularından biridir. Hem kentsel hemde kırsal ölçekte planlamalar, tasarımlar geliştiren meslek disiplini olarak peyzaj mimarlığı, ihtiyaçlara göre canlı ve cansız sistemleri besleyerek evrensel yaşam alanları ile yaşam çevrelerimizi geliştirirken, çok boyutlu projeler ile küresel çevre problemlerinin etkilerini azaltmayı hedefleyen alternatifler üretmektedir. Bu yüzden peyzaj mimarlığı eğitiminde öğrencilerin ekolojik düşünebilme becerisinin kazandırılması için ekolojik yaklaşımlı tasarım yöntemlerinin kalıcı olarak öğretilmesi oldukça önemlidir. Araştırmanın asıl amacı, öğrencilerin günümüz çevre problemlerine karşı fikir geliştirmesinde, tasarım algılarında ekolojik bilincin oluşmasında ve edindikleri bilgileri kullanabilmelerinde fakülteler arasındaki yaklaşım farklılıklarının etkisinin değerlendirilmesidir. Ayrıca çalışmada fakültelerin ağırlık verdikleri konuların farklılığının genel peyzaj mimarlığı tanımına olumlu etkileri tartışılmakta, peyzaj mimarlığı eğitiminde fakülte çeşitliliğinin öğrencilerin ekolojik bakış açısına sahip olma düzeylerini nasıl etkilediği, ders programlarının ekolojik yaklaşımlı tasarım oluşturulmasına yönelme durumu ve tasarım stüdyolarında ekolojik konuların kullanımını teşvik durumu değerlendirilmektedir. Araştırmanın öğrenci, öğretim elemanları, öğretim şekilleri ve fakültelerin müfredatına yönelik olarak gerçekleşmesi, peyzaj mimarlığı eğitimindeki güncel durumu değerlendirirken, yapılması planlanan değişiklikler veya gelecekte yapılabilecek önerileri ortaya koyması sebebiyle eğitim sisteminin gözden geçirilmesi noktasındaki çalışmalara katkı sağlamaktadır. Özellikte geçmiş literatür çalışmalarına göre, uluslararası ölçekte ekolojik tasarımın eğitim stratejileriyle birlikteliğini ortaya koyan çalışmalar bulunurken, Türkiye'de ancak güncel peyzaj mimarlığı eğitim durumunu ve derslerde öğrenci psikolojisini değerlendirmeye yönelik çalışmalar bulunması açısından önemli bir noktadadır. Bunun yanında ulusal ölçekte üniversitelerin müfredat sistemlerinden bahsedilirken, yerel kapsamda müfredatlar arasındaki farklılıkları ortaya koyan çalışmaların sınırlı olması açısından üzerinde dikkat edilmesi gereken bir konu olmaktadır. Dolayısıyla bu tez çalışmasının mevcut eğitim durumunun değerlendirilerek, gelecek için peyzaj mimarlığı eğitimine yönelik güncellemeler yapılması adına rehber görevi görmesi hedeflenmektedir. Bu amaçla peyzaj mimarlığının köklü fakülteleri olarak orman, ziraat, mimarlık ve güzel sanatlar fakülteleri bünyesinde yer alan üniversitelerin vizyon, misyon değerleri ile müfredat programlarının ders türleri, ders işleniş şekilleri mevcut durum analizi ile incelenmiştir. Müfredatların ekolojik boyutunun değerlendirilebilmesi açısından öncelikle ekoloji konulu dersler belirlenmiş ve bilgi-analiz-tasarım temelli yaklaşımla incelenmiştir. Buna göre fakültelerin yaklaşımlarına göre ekolojik yönden ağırlık durumları belirlenmiştir. Fakülte yaklaşımlarına müfredatların ders işleniş şekilleri ve ders durumlarına göre öğrencilerde ekolojik bilincinin kazanılmasını incelenmek için belirlenen fakülte öğrencileriyle anket çalışması gerçekleştirilmiştir. Araştırma sonuçlarına göre ekolojik tasarım kavramının gerektirdiği şartlar fakülte farklılığı gözetilmeksizin tüm öğrencilere aktarılabildiği fark edilmiştir. Fakat fakültelerin vizyon ve misyon değerleri, yaklaşımları, ders sayıları, derslerin teorik-uygulamalı olarak işlenişindeki değişimler, üniversite tarihçeleri, üniversite olanaklarına bağlı olarak değişim göstermektedir. Orman ve Ziraat fakülteleri farklı yönlerden ekolojik bilgiye, Mimarlık ve Güzel sanatlar fakülteleri ise ekolojik tasarım konusuna odaklanarak, kendi yaklaşımlarını nitelikli eğitimlerle öğretmeye çalışmaktadır. Güncel çevresel sorunlara değinilmesi ve ekolojik bilincin oluşumu noktasında ekolojik yöntem ve yaklaşımların tasarım süreçlerinde kullanımının Mimarlık ve Güzel Sanatlar fakültelerinde ön planda olduğu belirlenmiştir. Fakat tüm fakülte öğrencileri çevreye duyarlı çözümler geliştirmeleri gerektirdiğini bilerek öğrenimlerini tamamlamaktadır. Fakültelerin yaklaşımlarına göre ekolojik bilinç kazanımının farklı seviyelerde gerçekleştiği belirlenmiştir. Aynı şekilde teknik gezi, seminer, konferans gibi dersle ilişkili uygulamaların varlığı da fakültelere göre değişkenlik göstermekte ve ekolojik bilincin kazanımını etkilemektedir. Fakat konuyla ilişkili araştırma yapılabilecek ortam bulunma ve fiziksel tesis imkanı tümünde minimum düzeydedir. Fakültelerin ekolojiye farklı noktalardan değinmesi, kendi alanlarında nitelikli mezunlar vererek, mesleki anlamda çeşitliliğin sağlanması noktasında önemli olmaktadır. Fakat her mezunun aynı ekolojik bilince sahip olması ve ekolojik bilgi ve tasarım kavramını ilişkilendirilmesi, belirli oranda benzerlik yakalanması açısından minimum ölçekte standartların oluşumu gerekmektedir. Böylelikle her müfredat programında zorunlu olarak ekolojik verilerin doğal ve kültürel sistemler ölçeğinde uygulanması, değerlendirilmesi ve elde edinilen bu bilgilerin tasarım sürecine aktarılması ve kullanımları notasında öğrenciler desteklenmelidir.Sonuç olarak fakülte çeşitlilikleri ekolojiyi farklı yönlerden ele alması nedeniyle, ekolojik bilincin kazanımı noktasında ayrışmalara neden olsa da; mesleki ihtiyaçların karşılanması, çokyönlü bakış açısının devamlılığı için bu çeşitlilik korunması açısından oldukça önemlidir.

Landscape architecture education, which started for the first time in the world at Harvard University in the 1900s, has been included in the education programs of many local and national universities. The education system of landscape architecture developed with the ideas of Frederick Law Olmsted who accepted the father of the profession. However Jr Olmsted enabled that the landscape architecture education ideas become a student-accepted program. Architecture and landscape architecture students had an educational approach that took place on the building scale by taking common lessons during starting period in Harvard education academic term. The developing new discipline reached Europe and started in 1919 at the University of Norway. The education system focused on the herbal design of small-scale gardens caused the aesthetic and beautiful perception to be included in the program with the effect of the 1919 First World War. The ongoing education program with the effect of modernization, started to form its own special structure and a system in which the aesthetic and natural structure came together was determined within the design school of Harvard University. The inclusion of fine arts that developed under the influence of modernization in the landscape architecture education system enabled it to reach global dimensions from Europe after 1950. The advancing discipline in Europe and North America, which was first developed in the Asian continent due to the effects of the Second World War, was realized under the influence of modernization with the support of European educators. The spreading of the education program over the world, has enabled the expanding design perception from tha garden to the urban scale. Transformed approach of landscape architecture education, which started to globalize in Asia, has found novel places in South America, Africa and Austria with the effect of European modernization educators. The perspective of landscape architecture profession has changed with the increase of environmental problems in the world after modernization. The increasing interest in the profession also increased the importance given to landscape architecture education. The current state of nature has been adopted with analysis-based approaches, focusing on identifying needs related to the nature-human relationship in the education programs. Launched unprecented period of ecology-design relationship with the inclusion of satellite images and computer programs, was established analysis-synthesis approach into the education system. the concept of ecology-technology-design was associated with the concept of sustainability at the end of the period, So the aims of design approaches were reuse brownfield, inert urban areas. These ecology-based approaches vary depending on universities and faculties in landscape architecture education. The differences in curriculum, vision, mission and course methods according to the faculties cause universities to develop different approaches and perspectives to current environmental problems in landscape architecture education. While some faculties focus on the conservation and planning of vegetative materials, some focus on landscape design and some on the implementation of landscape projects. However, it should not be forgotten that a landscape architect graduates by accepting experts in all the above-mentioned fields and must be able to perform his profession in any condition and environment. Developing ecologically-based sustainable approaches by considering people's need for nature together with natural balance by landscape architects are important issue in the landscape architecture profession. As a profession discipline that develops planning and designs on both urban and rural scale, it produces purposed alternatives to reduce impacts of global environmental problems with multi-dimensional projects while developing the world with its universal living spaces by feeding live and inanimate systems according to the needs. Therefore, it is possible to provide students with the ability to think ecologically in landscape architecture education through permanent teaching of ecological based design methods. The main purpose of the study is to evaluate the effect of the differences of approaches among the faculties in developing students' ideas against environmental problems, creating an ecological awareness in their design perceptions and using the information which they have acquired. Also, to discuss the positive effects of the difference of the subjects that faculties emphasize on the definition of general landscape architecture, how faculty diversity affects students' level of ecological perspective in landscape architecture education. To evaluate the course programs' tendency towards creating an ecological approach and the incentive of using ecological issues in design studios. The realization of the research towards students, academicians, teaching methods and the curriculum of the faculties is very critical in revising the education system, as it evaluates the current situation in landscape architecture education, as it reveals the planned changes or future suggestions. According to previous literature on the property, although the studies demonstrated the association with educational strategies of ecological design have on an international scale, there are the only current situation landscape architecture education in Turkey and studies to assess the students in psychology courses. So this study is critical issue to evaluate in terms of the Turkey's ecological dimension of landscape architecture education. In addition, while talking about the curriculum systems of universities on an international scale, there is restricted that demonstrates the differences between the curricula in the local context. Therefore, this thesis study can be a guideline making updates for future landscape architecture education programs by evaluating existing education situation. According to the results of the research, if the concept of ecological design is expressed clearly in the curriculum, the student has be aware of learning regarding ecology and ecological design. Otherwise, students are not consious of learning despite existing several ecology based courses. Required conditions in the concept of ecological design can be transferred to all students regardless of faculty differences according to the results of the research. Therefore, faculty difference isn't a factor to excite the common consciouness about design perception of ecology. However, the vision and mission values of faculties, their approaches, the number of lessons, the changes in the theoretical and practical processing of the courses, have been determined the interpretation of the knowledge of the faculties of Architecture & Fine Arts in terms of ecology and their design aspects, and the different aspects of the ecological knowledge of Forestry and Agriculture faculties, by considering different aspects of ecological knowledge. The high number of applied courses in the curriculum programs regarding the processing and use of ecological information indicates that the student remains longer. Since design studios are the most important of the practical lessons in the education process, the qualifications they gain should be on developing an ecological perspective. According to the study, all faculty students can gain environmental awareness and develop environmentally conscious design suggestions. But, all faculties doesn't have enabled critical, creative, determined and self-confident individuals towards ecological design. According to evaluated results, Architecture & Fine Arts faculties pay more attention to the use of ecological methods and approaches in design processes, addressing current environmental problems and the formation of ecological awareness than faculties of Agriculture & Forestry. So, the prominent result of the design studios is the development of innovative solutions for the present day and determination that they are provided in the faculties of Fine Arts and Architecture. Landscape architecture department of conditions in Turkey can show that the ecological approach to development within the framework of existing facilities. The realization of the applications related to the course such as technical trips, seminars, conferences in terms of raising ecological awareness varies according to the faculties, while the whole universities have provided minimum opportunities to own a research environment and physical facilities regarding the ecology. As the faculties are important in handling the courses of different perspectives in the relation of ecology to provide professional diversity and qualified graduates in their fields. Still, an essential is that each graduate has the same ecological awareness, and to associate ecological knowledge and design need to be certain standards in curricula. Thus, in every curriculum program, the use of ecological data on the scale of natural and cultural systems must be essential in order to transfer for the design process and the use of these data by students should be supported through academics. All universities prepare curriculum with multi-disciplinary approaches according to the global landscape architecture education conditions. Therefore, only mission & vision values are not pioneers in the development of the ecological approach. Other factors, such as management, historical development, and its location, shape the current structuring of faculties. Every graduate can make designs with ecological consciousness under all conditions, but according to the current perspective, the state of being ecological can vary. As a result, although the faculty diversity enables to handle ecology from different perspectives and causes differences at the point of raising ecological awareness, this diversity must be preserved to meet professional needs and to maintain a multi-faced perspective.
Evaluation of the ecological dimension of landscape architecture education in the faculty framework
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: eğitim ve öğretim; education and training; peyzaj mimarlığı; landscape architectur